Credit Chains and Sectoral Comovement : Does the Use of Trade Credit Amplify Sectoral Shocks? - Raddatz, Claudio (2012)
This paper provides evidence of the presence and relevance of the credit chain propagation and amplification mechanism described by Kiyotaki and Moore (1997) by looking at its implications for the correlation of industries. In particular, it tests the hypothesis that an increase in the use of trade credit, along the input-output chain linking two industries, results in an increase in their output correlation using detailed data on the correlations and input-output relations of 378 manufacturing industry pairs across 43 countries with different degrees of use of trade credit. The results provide strong support for this hypothesis and indicate that the mechanism is quantitatively relevant.